2009
DOI: 10.1108/14678040910949675
|View full text |Cite
|
Sign up to set email alerts
|

Libraries, telecentres and cybercafés

Abstract: PurposeThis paper aims to offer early insight into ongoing research comparing public access venues such as libraries, cybercafés and telecentres in 25 countries around the world.Design/methodology/approachThe authors studied information needs and uses of information and communication technologies (ICT) in these public access venues, with a particular focus on underserved populations.FindingsUnderstanding trends, differences and similarities across venues and across countries offers an emerging map that will he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another implication for developing countries has to do with trying to explain the reasons behind the failure of one of the most common initiatives policy-makers and private organizations have developed in order to foster ICT adoption and use in developing countries, the telecenters or information kiosks (Gomez et al 2009). These telecenters and information kiosks should enable "poor people to receive information about their governments, market prices, health and education" (Ashraf et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another implication for developing countries has to do with trying to explain the reasons behind the failure of one of the most common initiatives policy-makers and private organizations have developed in order to foster ICT adoption and use in developing countries, the telecenters or information kiosks (Gomez et al 2009). These telecenters and information kiosks should enable "poor people to receive information about their governments, market prices, health and education" (Ashraf et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, community networks need strategies to mitigate sociocultural issues. Trust in technology: Trust in technology is needed if people are to realize the full benefits of access to ICTs (Gomez, Ambikar and Coward, 2009).…”
Section: Development Of a Framework To Assess A Community Network Ecosystemmentioning
confidence: 99%
“…In Latin America, public-access centres take one of three forms: libraries, cybercafés, or telecentres (Gomez, Ambikar, & Coward, 2009), where a telecentre is "a public place where people can find information, create, learn, and communicate with other while developing digital skills through access to information and communication technology" (Telecentre Foundation, 2016). As providers of physical access to the Internet and ICTs, these public centres are ideally situated to collect sexdisaggregated data and generate relevant statistical information about user interactions with digital technologies.…”
Section: Libraries As Information Gatherersmentioning
confidence: 99%
“…While regional initiatives are being undertaken to improve women's representation in the fields of science, technology, and engineering (Parmentier & Huyer, 2008), the persisting disparity requires action from local public institutions. Although community-based telecentres are often championed over libraries as the preferred points of access (see Gomez, Ambikar, & Coward, 2009;Gomez, & Gould, 2010), testimonies from women have revealed that "without explicitly addressing the needs of women users, telecentres…do not achieve their objectives of providing access to technology to communities and women in particular" (Huyer & Sikoska, 2003, p. 19). With telecentres struggling to provide equal and equitable opportunities of access to and use of the internet and ICTs, the reintroduction of libraries into the equation as suitable collaborative partners becomes increasingly desirable.…”
Section: Libraries As Instructors and Educatorsmentioning
confidence: 99%